Natural history and survival of 14 patients with corticobasal degeneration confirmed at postmortem examination. Issue 2 (1st February 1998) - Wenning, G K; Litvan, I; Jankovic, J; Granata, R; Mangone, C A; McKee, A; Poewe, W; Jellinger, K; Chaudhuri, K Ray; D'Olhaberriague, L; Pearce, R K B
Abstract : OBJECTIVE: To analyse the natural history and survival of corticobasal degeneration by investigating the clinical features of 14 cases confirmed by postmortem examination. METHODS: Patients with definite corticobasal degeneration were selected from the research and clinical files of seven tertiary medical centres in Austria, the United Kingdom, and the United States. Clinical features were analysed in detail. RESULTS: The sample consisted of eight female and six male patients; mean age at symptom onset was 63 (SD 7.7) years, and mean disease duration was 7.9 (SD 2.6) years. The most commonly reported symptom at onset included asymmetric limb clumsiness with or without rigidity (50%) or tremor (21%). At the first neurological visit, on average 3.0 (SD 1.9) years after symptom onset, the most often encountered extrapyramidal features included unilateral limb rigidity (79%) or bradykinesia (71%), postural imbalance (45%), and unilateral limb dystonia (43%). Ideomotor apraxia (64%), and to a lesser extent cortical dementia (36%), were the most common cortical signs present at the first visit. During the course of the disease, virtually all patients developed asymmetric or unilateral akinetic rigid parkinsonism and a gait disorder. No patient had a dramatic response to levodopa therapy. Median survival time after onset of symptoms was 7.9 (SD 0.7) (range, 2.5–12.5) years, and, after the first clinic visit, 4.9 (SD 0.7) (range, 0.8–10) years. Early bilateral bradykinesia, frontal syndrome, or two out of tremor, rigidity, and bradykinesia, predicted a shorter survival. CONCLUSION: The results confirm that unilateral parkinsonism unresponsive to levodopa and limb ideomotor apraxia are the clinical hallmarks of corticobasal degeneration, and only a minority of patients with corticobasal degeneration present with dementia. The study also suggests that a focal cognitive and extrapyramidal motor syndrome is indicative of corticobasal degeneration. Survival in corticobasal degeneration was shortened by the early presence of (more) widespread parkinsonian features or frontal lobe syndrome.